Portraying Students’ Critical Thinking: A Case Study of Information Technology Students - Agnes Widyaningrum; Kristophorus Hadiono; Felix Andreas Sutanto (Soegijapranata Catholic University, 2022)
Abstract— Students’ critical thinking is one of the life skills that they have to master in their life. The shifting means of reading, from textbooks to electronic text tends to change students’ behavior. They are lazy to read from the text on the other hand they are keen to read through gadgets. Reading is one of the strategies to build critical thinking in which students have to improve their understanding so that they know about the things written in the texts. Though the COVID-19 pandemic changes the reading mode, the students’ comprehension is still low. This study is a preliminary study for portraying students’ critical thinking from Information Technology students, about critical thinking, known as a case study. The findings show that the students’ comprehension is low. Among seven (7) traits of critical thinkers proposed by Martha Stewart, they show that the systematic-by-the method trait is the dominant trait because they rely on their logical reasoning. Based on Bloom Taxonomy, the result shows that their cognitive level is on the level of understanding that belongs to young learners’ level. The conclusion shows that the students of Information Technology are dominant in the systematic-by-the method trait. They should improve their reading level by spending more reading time and practicing their comprehension from reading different texts. By reading, the students will gain knowledge of the world and be critical thinkers.